Remeasuring Annapurna I: Geospatial Innovation and the Quest for Precision (Journal on Geoinformatics, Nepal, 2025)
Mount Annapurna I, the world’s tenth-highest peak and a geographic jewel of Nepal, has long captivated scientists, mountaineers, and mapmakers. Despite its significance, the mountain’s officially recognized elevation- 8,091 meters—has been derived from legacy survey that vary in accuracy and methodology. In light of recent advances in geodetic science, tectonic shifts, and climate-induced landscape changes, a modern remeasurement of Annapurna I is both timely and necessary. This article explores the historical context of its elevation estimates, the scientific and technological rationale for remeasurement, and the broader geophysical, cartographic, and cultural implications. It argues that a new measurement campaign, leveraging Global Navigation Satellite System (GNSS), satellite gravimetry, and aerial photogrammetry, would enhance national geospatial data infrastructure, support environmental monitoring, and reaffirm Annapurna’s place in global geoscientific research.